Mixed reality and real-life exercises for mass casualty incidents: a comparison of psychological responses and learning - Baetzner, Anke; Gerwann, Solène; Uhl, J. C.; Schuster, B.; Sjöberg, D.; Wenighofer, R.; Frenkel, Marie Ottilie; Wrzus, Cornelia (Educational technology research and development, 2025)
Well-prepared medical first responders (MFRs) are indispensable for effectively managing mass casualty incidents (MCIs). Still, the gold standard for training, high-fidelity real-life exercises (RLEs), is infrequently implemented due to high organizational effort and costs. Mixed reality (MR), where MFRs train in a virtual environment with haptic feedback from manikins, may be a viable training alternative. This study aimed to explore strengths, limitations, and potentials for improvement of MR-MCI training in relation to two RLEs. Thirty-four MFRs (Mage = 29.7, SDage = 7.7, 82% male) participated in MR training, 14 MFRs in RLEs (RLE1, akin to MR: n = 4, Mage = 32.0, SDage = 9.5; RLE2, near-ideal: n = 14, Mage = 26.9, SDage = 6.7; 100% male). Stress, exhaustion, self-efficacy, presence, and perceived learning gain were assessed using questionnaires and analyzed descriptively. Participants further answered open-ended questions about perceived opportunities and limitations of virtual training. The MR and RLE groups reported similar stress, exhaustion, and self-efficacy levels. The MR group reported slightly lower physical presence but considerably lower social presence than the RLE groups. Perceived learning gains were moderate for MR participants and high for RLE participants. Qualitative data indicated a need to improve interaction opportunities with virtual patients. Also, participants viewed virtual training as a resource-efficient supplement, not a replacement for RLEs. Future studies should explore which content and groups benefit most from MR and further evaluate it through larger, experimental studies. MR-MCI training shows promise in preparing MFRs for MCIs and seems to be a valuable addition to RLEs, with the potential to increase training frequency and practice scenarios otherwise difficult to simulate.